2021
DOI: 10.7717/peerj.11932
|View full text |Cite
|
Sign up to set email alerts
|

The effect of uncorrected ametropia on ocular torsion induced by changes in fixation

Abstract: Background and Objective Ocular torsion, the eye movements to rotating around the line of sight, has not been well investigated regarding the influence of refractive errors. The purpose of this study was to investigate the effect of uncorrected ametropia on ocular torsion induced by fixation distances. Methods Seventy-two subjects were classified according to the type of their refractive error, and ocular torsion of the uncorrected eye was compared based on changes induced by different fixation distances. Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…It is worth noting that DFA has been shown to have a positive association with age 27 , 28 . Additionally, there was an increase in extorsion observed in patients with uncorrected myopia and astigmatism 29 . However, some researchers have reported that DFA was not associated with age or refractive error in children 17 , 30 .…”
Section: Discussionmentioning
confidence: 90%
“…It is worth noting that DFA has been shown to have a positive association with age 27 , 28 . Additionally, there was an increase in extorsion observed in patients with uncorrected myopia and astigmatism 29 . However, some researchers have reported that DFA was not associated with age or refractive error in children 17 , 30 .…”
Section: Discussionmentioning
confidence: 90%